Activating STAT3 mutations in CD8+ T-cells correlate to serological positivity in rheumatoid arthritis - Moosic, Katharine B.; Olson, Thomas L.; Freijat, Mark; Khalique, Samara; Hamele, Cait E.; Shemo, Bryna; Boodoo, Jesse; Baker, William; Khurana, Gitanjali; Schmachtenberg, Matthew; Duffy, Tristin; Ratan, Aakrosh; et al. (Frontiers in Immunology, 2024)
Objectives Large granular lymphocyte (LGL) leukemia is a rare hematologic malignancy characterized by clonal expansion of cytotoxic T-cells and frequent somatic activating STAT3 mutations. Based on the disease overlap between LGL leukemia and rheumatoid arthritis (RA) and a putative role for CD8+ T-cells in RA, we hypothesized that STAT3 mutations may be detected in RA patient CD8+ T-cells and correlate with clinical characteristics. Methods Blood samples, clinical parameters, and demographics were collected from 98 RA patients and 9 healthy controls (HCs). CD8+ cell DNA was isolated and analyzed via droplet digital (dd)PCR to detect STAT3 mutations common in LGL leukemia: Y640F, D661Y, and the S614 to G618 region. STAT3 data from 99 HCs from a public dataset supplemented our 9 HCs. Results RA patients had significantly increased presence of STAT3 mutations compared to controls (Y640F p=0.0005, D661Y p=0.0005). The majority of these were low variant allele frequency (VAF) (0.008-0.05%) mutations detected in a higher proportion of the RA population (31/98 Y640F, 17/98 D661Y) vs. HCs (0/108 Y640F, 0/108 D661Y). In addition, 3/98 RA patients had a STAT3 mutation at a VAF >5% compared to 0/108 controls. Serological markers, RF and anti-CCP positivity, were more frequently positive in RA patients with STAT3 mutation relative to those without (88% vs 59% RF, p=0.047; 92% vs 58% anti-CCP, p=0.031, respectively). Conclusions STAT3 activating mutations were detected in RA patient CD8+ cells and associated with seropositivity. Thus, STAT3 activating mutations may play a role in disease pathogenesis in a subset of RA patients.